Body weight perception versus body weight status, How good is the agreement - Jamani, Nurjasmine Aida; Said, Abdul Hadi; Abd. Aziz, Karimah Hanim; Abd Rahman, Mohd Aizuddin (2018)
Body weight perception is an important underlying psychological factor associated with body weight.